Nicho ecológico e áreas prioritárias para a conservação de camarões Peneídeos (Decapoda; Penaeidae) ao longo da região costeira afetada pelo rejeito da barragem de Fundão (Mariana-MG) - Pereira, Wanessa Gomes (2022)
The Fundão dam, belonging to the Samarco company in the city of Mariana (MG), disrupted on 5th of November 2015 inserting, anthropically, approximately 45 million m³ of tailings containing mainly iron ore into the environment. Thirty-nine cities in the states of Minas Gerais and Espírito Santo were affected, more than 600 km were covered by tailings from the mine along the Doce River and its tributaries until reaching the Atlantic Ocean. In the coastal zone, the mud reached five marine protected areas (MPAs): Área de Proteção Ambiental (APA) Costa das Algas, Parque Nacional (PARNA) Marinho dos Abrolhos, Reserva Biológica (REBIO) de Comboios, Reserva Extrativista (RESEX) de Cassurubá e Refúgio de Vida Selvagem (REVIS) de Santa Cruz. The tailings from the dam failure exerted, and still can exert, influence on the entire environment. Monitoring indicated unprecedented contamination of fish and crustaceans by metals, both in the river and on the adjacent coast. Given this scenario, several species of fauna were directly and indirectly affected, including penaeid shrimps, which have ecological and relevant economic importance. Although the benefits generated by fishing these crustaceans, the impacts on the marine environment have become a source of concern in the management of this resource. The situation becomes even more critical when added to environmental degradation and pollution, as in the case of the Fundão dam failure. Thus, in the first chapter the potential distribution of crustacean species of the Penaeidae family was evaluated in the coastal region affected by the tailings of the Fundão dam, through ecological niche modeling. In the second chapter, we discuss places that could possibly be used for the restoration and conservation of penaeid populations in the affected region, besides measure the potential impact of the tailings on the species. The results obtained in the present study may contribute to a better understanding of the spatial distribution of penaeids in the impacted area, considering the scarcity of such information in this region. They can also assist in directing measures aimed at restoring and conserving these shrimp populations.